Patterns of ostracod migration for the 'North Atlantic' region during the Ordovician - Williams, M; Floyd, J; Salas, M; Siveter, D; Stone, P; Vannier, J (2003)
A review of Ordovician neritic ostracods from the 'North Atlantic' region including Europe and North America identifies over 100 genera (including 44 palaeocopes and 31 binodicopes) which show a complex pattern of migration between two or more of the palaeocontinents Gondwana, Ibero-Armorica, Perunica, Avalonia, Baltica and Laurentia. Many dispersals were relatively slow, and the migration of a genus between palaeocontinents often took the duration of one or more graptolite biozones. Over 70 migrations appear to have occurred more rapidly, including those of Pseudulrichia, a genus which dispersed to five palaeocontinents within the duration of three graptolite biozones. Longevity clearly facilitated the chances of migration, as the most widespread genera such as Vannieria, Platybolbina, Medianella and Euprimites, are often the most long-ranging. Low migration rates prior to the Llanvirn are, at least in part, related to low ostracod taxonomic diversity. Greatly increased diversity from the late Llanvirn coincided with a much higher rate of migration. Coupled with the spread of carbonate-mudstone shelf marine facies in Laurentia during the early and mid Caradoc, this resulted in the migration of up to 18 Baltic-origin genera to Laurentia. Relative to overall ostracod diversity, migration rates were generally higher during periods of lower global sea level, suggesting that ostracod dispersal may have been aided by mid-ocean islands or outer-shelf carbonate platforms, which provided more extensive island-hopping routes during periods of low sea level. The palaeogeographical convergence of Avalonia, Perunica and Baltica, and subsequently of Avalonia and Baltica with Laurentia, in low latitudes and warm surface waters, is suggested by increasing ostracod migration between these palaeocontinents from the late Llanvirn onwards. This culminated, during the Ashgill, in numerous species-level links. Baltica may have been the source area for more than 40 migrant genera, reflecting its high-diversity faunas and its intermediate palaeogeographical position between Laurentia and Avalonia. Several ostracod genera used Baltica as a staging-post in migrations between Avalonia and Laurentia. Migrations continued during the late Ashgill Hirnantian Stage (24 migrations), especially between Laurentia, Baltica and Avalonia (up to 19 migrations of genera), suggesting close geographical proximity for these palaeocontinents. Some ostracods, particularly the binodicopes Pseudulrichia, Klimphores, Kinnekullea, Aechmina and Spinigerites, could occupy outer-shelf and cooler-water benthic palaeoenvironments. They were part of a widespread deep-shelf fauna from the mid Caradoc onwards, for which distances or climatic barriers were less of an obstacle for trans-oceanic migration. None of these ostracods were bathyal. © 2003 Published by Elsevier Science B.V.